A MAP OF VULNERABILITY TSUNAMI AND PLAN EVACUATION IN COASTAL VILLAGE OF PARANGTRITIS SUB-DISTRICT KRETEK DISTRICT BANTUL DAERAH ISTIMEWA YOGYAKARTA - Gentur Handoyo; Agus A.D. Suryo Putro; Petrus Subardjo (Jurnal Kelautan, 2017)
ABSTRACTThe tsunami often hitthe southern coast of Java several times, where Parangtritis located in that area. This is due to the meeting of Indo-Australian plate with the Eurasian plate in the south of Java that results in a major tectonic tsunami source. Tsunami waves from this region takes 50 to 100 minutes to reach the beach. Considering the short span of time to self-rescue, than its necessary to concieve a map of vulnerability to the tsunami region to plan evacuation routes and tsunami temporary evacuation place (TES) tsunami incoastal village of Parangtritis. The material used as an object to study in this research is the vulnerability of the tsunami, tsunami runoff based on the runup height, the proposed evacuation routes and tsunami temporary evacuation place (TES) as. The result,village in Parangtritis is a tsunami prone areas with vast percentage of the tsunami-prone areas at 66.45%. When the tsunami run up reach 16m the affected area was 788.07 Ha. There are three proposed evacuation route through the Parangtritis roads, Depok roads and Depok-Parangtritis roads. There are 12 proposed temporary evacuation place which spread in the village Parangtritis. Keywords: Inundation, Plate, Runup